Therapeutic Updates on Lichen planopilaris and Frontal Fibrosing Alopecia: A Systematic Review - Behnoush Bakhshoudeh; Maryam Salehi; Ramin Sadeghi; Alireza Omranzadeh; Toktam Sahranavard; Soheil Arekhi; Ali Jafarzadeh Esfehani; Naghmeh Zabolinejad (Reviews in Clinical Medicine, 2018)
Introduction: Lichen planopilaris (LPP) and frontal fibrosing alopecia (FFA) are skin diseases that affect the quality of life. Although a systematic review on LPP and FFA treatment was published in 2013, further updates are needed. The aim of this study is to review systematically the studies published after the last systematic review.Methods: We searched Scopus, PubMed, Embase, and ISI Web of Science. All the studies published during March 2012-June 2017 were included in this review. Two reviewers separately selected the studies and extracted the data. The results of studies were categorized as unimproved, stabilized, and improved based on the articles reports.Result: Among the 38 studies, 20, 17, and one studies assessed LPP, FFA, and both treatments, respectively. The papers were case reports, case series, cohorts, and randomized controlled trials. Antimalarial agents and pioglitazone resulted in enhancement in 73 and 71% of the LPP patients, respectively. Improvement and stabilization were observed in almost one third of the topical steroid users and 6/12 of Tacrolimus/Pimecrolimus users in LPP. Improvement and stabilization in FFA was found in 68% of the individuals using antimalarial agents, 83% of intralesional steroid users, all cases of finasteride users, and 95% of the people utilizing dutasteride.Conclusion: Contrary to the previous systematic review, we found antimalarial agents more effective than steroids in LPP. Finasteride/dutasteride may have favorable impacts on FFA. Intralesional steroids showed to be more effective than antimalarial agents in FFA. Still further studies are needed in order to define a treatment protocol. Low quality and heterogeneity of the articles were among the limitations for making a conclusion.